Grisars reaktion på luftfyllt skum - Thurehult, Åsa (2019)
There are a majority of approved stunning methods for pig slaughter in Sweden. These include captive bolt stunner, rifles (including shotguns), electricity and carbon dioxide. Carbon dioxide and electricity are among the most common methods.